Meliponini neotropicais: o gênero geotrigona moure, 1943 (apinae, apidae, hymenoptera), com especial referência à filogenia e biogeografia - Camargo, João M. F.; Moure, Jesus S. (Arquivos de Zoologia, 1996)
The Neotropical genus Geotrigona Moure is revised. Five species (G. argentina, sp. n., G. xanthopoda, sp. n., G. fulvatra, sp. n., G. fumipennis, sp. n., G. lutzi, sp. n.) and four subspecies (G. lutzi terricola, ssp. n, G. subgrisea subfulva, ssp. n., G. subgrisea kwyrakai, ssp. n., G. subgrisea tellurica, ssp. n.) are new for science. The sixteen recognized species constitute four monophyletic subgroups or clades: Subterranea group (monotypic): G. subterranea (Friese, 1901); Mombuca group: G. mombuca (Smith, 1863), G. argentina, G. mattogrossensis (Ducke, 1925), G. aequinoctialis (Ducke, 1925), G. xanthopoda and G. fulvatra; Fulvohirta group: G. fulvohirta (Friese, 1900), G. fumipennis, G. acapulconis (Strand, 1919), G. leucogastra (Cockerell, 1914), G. chiriquiensis (Schwarz, 1951), G. lutzi and G. lutzi terrícola; Subgrisea group: G. sibgrisea subgrisea (Cockerell, 1920), G. subgrisea subfulva, G. subgrisea kwyrakai, G. subgrisea tellurica, G. subnigra (Schwarz, 1940) and G. kraussi (Schwarz, 1951). Lectotypes are designated for G. mombuca, G. aequinoctialis, G. leucogastra and G. subgrisea subgrisea; the holotype and paratypes of G. subnigra, G. kraussi and G. chiriquiensis, respectively, are studied. G. subterranea and G. fulvohirta are interpreted based on specimens probably from type series. G. mattogrossensis and G. acapulconis are interpreted based on the literature. Geotrigona subterranea, G. mombuca, G. mattogrossensis, G. aequinoctialis, G. fulvohirta, G. acapulconis, G. chiriquiensis and G. kraussi are subterranean nesting stingless bees. For the other ones there is no information. The congruence between the geographic distribution patterns and phylo-genetic hypothesis suggests that no more than 6 cladogenetic events determined the whole present diversity of Geotrigona. The following sequence of disjunction or vicariance events is postulated: 1, the Atlantic-southeast region of Brazil (Subterranea clade) separates from the other places of Neotropical region (other Geotrigona); 2, the Neotropical region divides into two large tracks - SE of South America, southern of the alignment of Amazonas and Madeira rivers (Mombuca clade) an Nof South America, Panama, Central America and southern Mexico (other Geotrigona); the NIV track subsequently subdivides into three smaller tracks that originates the more derived clades of Geotrigona; 3, eastern Amazon (Subgrisea clade), western (other Geotrigona) and 4, western Amazon (Fulvohirta clade) separates from the extreme northwest of South America, Panama, Central America and southern Mexico (Leucogastra subclade, along the Pacific coast from Equador to the southwest of Mexico); 5,6, the last two events (climatic!) to cause vicariance, which possibly reached simultaneously the whole Neotropical region, determined the origin of the terminal taxa. The three main groups of Geotrigona (Mombuca, Subgrisea and Fulvohirta groups) overlap only along the region of extreme Western Amazonia (Bolivia, Peru). This biogeographic pattern, if extensive to other groups of organisms, may explain the great faunistic diversity found in this region. Identification key for species and drawings for the main characters are given.